(untitled) (Research, Society and Development, 2021)
The new policies to release recreational cannabis use in recent decades have increased the use in food. As it is a relatively new and promising market, patent protection is necessary. This manuscript aimed to map patent technologies regarding the addition of cannabis or cannabidiol to food products, with the purpose of verifying technological advances and national and international market trends. A documentary research was carried out, through patent documents, in the INPI electronic database and with the aid of the ORBIT® software, from Questel. It was possible to verify an increase in the number of deposits from 2012, indicating that the release of recreational use has heated up the study and development of technology. It was observed that, both nationally and globally, the main patent filers are private companies and that most of the patents deposited are defined as active. This shows how incipient the technology is and promises great innovations. The protection of these patents occurs mostly in China, the United States and Canada.